2018
DOI: 10.1002/dev.21803
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of gut‐immune‐brain mechanisms in Autism Spectrum Disorder

Abstract: Despite decades of research, the etiological origins of Autism Spectrum Disorder (ASD) remain elusive. Recently, the mechanisms of ASD have encompassed emerging theories involving the gastrointestinal, immune, and nervous systems. While each of these perspectives presents its own set of supporting evidence, the field requires an integration of these modular concepts and an overarching view of how these subsystems intersect. In this systematic review, we have synthesized relevant evidences from the existing lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 250 publications
(414 reference statements)
1
37
0
2
Order By: Relevance
“…Metabolic abnormalities have been reported in ASD (7), though most have measured a small subset of metabolites and many outcomes have not reproduced between cohorts. Mitochondrial dysfunction, which heavily influences systemic metabolism, is estimated to be higher in ASD than controls (5% vs ~0.01%) (8), and genes crucial for mitochondrial function are risk factors for ASD (9).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic abnormalities have been reported in ASD (7), though most have measured a small subset of metabolites and many outcomes have not reproduced between cohorts. Mitochondrial dysfunction, which heavily influences systemic metabolism, is estimated to be higher in ASD than controls (5% vs ~0.01%) (8), and genes crucial for mitochondrial function are risk factors for ASD (9).…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of the gut microbiota in ASD has been conceptualized starting from several lines of evidence. First of all, the prevalence of gastrointestinal (GI) symptoms has been found to be higher in ASD subjects compared to typically developing (TD) peers ( 9 12 ). Then, several studies showed a significant dysbiosis and a change in the stability, diversity, composition and/or metabolism of the gut microbiota in ASD children compared to TD peers ( 13 , 14 ), while others reported disrupted intestinal permeability in ASD subjects ( 15 , 16 ), and evidence of a systemic and intestinal inflammation in ASD [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although differentiation is mostly driven by immune signals such as chemokines or cytokines, the Treg/Th17 balance could be influenced by an altered microbiota. Indeed, differentiation into Treg can be induced by some species of Clostridiales and by Bacteroides fragilis, whereas the differentiation into Th17 cell can be induced by some segmented filamentous bacteria (SFB) [82].…”
Section: Clinical Evidencementioning
confidence: 99%